Management of a trauma patient with alcohol withdrawal who developed neuroleptic malignant syndrome in Korea: a case report - Byungchul Yu; Ji Yeon Lee; Yong Beom Kim; Hee Yeon Park; Junsu Jung; Youn Yi Jo (Journal of Trauma and Injury)
Neuroleptic malignant syndrome (NMS) is a rare but fatal condition, with a high mortality rate. NMS is characterized by altered mental status, fever, myoclonus, autonomic dysfunctions, and elevated creatinine phosphokinase. The clinical manifestations may be confused with alcohol-related symptoms, trauma, sepsis, postoperative agitation, or malignant hyperthermia. A 69-year-old male patient with alcohol withdrawal was admitted to the operating theatre to rule out septic shock due to mesenteric injury after multiple trauma. He was suspected NMS with abrupt increase body temperature to 41.7°C after haloperidol administration. Active cooling and rapid fluid infusion was done during anesthesia. Delayed diagnosis and treatment of NMS lead to catastrophic result. Therefore, if the patient's past medical history is unknown or clinical symptoms develop that are suggestive of NMS, early treatment must be considered.